TATA KELOLA SEDIAAN FARMASI PADA MASA PANDEMI COVID 19 DI PUSKESMAS TANJUNG MORAWA KECAMATAN TANJUNG MORAWA KABUPATEN DELI SERDANG - Sembiring, Hedni Febrianty; Samran, Samran; Gurusinga, Rahmad (NHM PRESS, 2023)
Management Drug management consists of Planning, Procurement, Receiving, Storage, Distribution,Control, Recording and reporting, During the Covid 19 pandemic, the demand for drug for this reason it is necessary to do good drug management. This information in this study were the Head of public Health Center, Head of Drug Warehouse, Drug Warehouse Installation Staff, and Health Installation Staff of Tanjung Morawa Helath Center, Deli Serdang Regency and from the data in triangulation. This research was data collection was carried out by means of in depth interviews and questionnaires. Data analysis by identifying problems using fishbone diagrams so that a casual relationship is obtained. The result of this study indicate that an exper profesional in drug management is very necessary, in order to achieve drug management in accoordance with the Minister of Health Regulation, the lack of cabinets is also an obstacle in drug management, at lack of facilities and in frastructure in the Public health center is contained in electronic devices such as computers so that in recording and repoting drugs there are still manually. It is recommended that the implementation of drug management based on the Regulation of the Minister of Hhelath regarding Technical Instruction for Standar Pharmacy Services for Helath Center in 2019 be maintauned.